Chinese herbal medicine (Rupi Sanjie capsule) for the treatment of breast pain: A systematic review and meta-analysis of randomized clinical trials - Bao-Yong Lai; Li-Yan Jia; Bo-Wen Yu; Shi-Bing Liang; Ai-Jing Chu; Hui-Juan Cao; Jian-Ping Liu; Xiao-Hua Pei (Integrative Medicine Research)
Background: Breast pain is one of the most common breast disorders, affecting 41%–69% women in the clinical populations. Chinese herbal medicine (Rupi Sanjie, RPSJ) capsule has been recommended to be commonly used for breast pain in China. This review aimed to systematically collect latest evidence and critically evaluate the eﬀ ;ectiveness and safety of RPSJ capsule for breast pain. Methods: We searched 6 databases from their inception to June 1, 2020 for randomized clinical trials (RCTs) comparing RPSJ capsule with conventional drug therapies, placebo or no treatment. Primary outcomes were breast pain relief, reduction of breast mass and clinical cure rate. Results: Seventeen RCTs were included in total, involving 2899 participants with breast pain. RPSJ capsule showed a significant effects in shortening duration of the breast pain (MD-6.51 days, 95%CI [-8.57, -4.45], n = 82, 1 trial), shortening the duration of breast mass (MD-5.17 days, 95%CI [-7.56, -2.78], n = 82, 1 trial), improving clinical cure rate (RR 1.55, 95% CI [1.21, 2.00], I² = 64%, n = 1398, 10 trials) and total effective rate (RR 1.08, 95% CI [1.03, 1.14], I² = 71%, n = 2170, 14 trials) compared to Tamoxifen (TAM). The meta-analysis showed that the incidence of total adverse events was higher in TAM group than the RPSJ capsule group (RR 0.30, 95%CI [0.21, 0.42], I² = 49%, n = 2122, 13 trials). Conclusions: RPSJ capsule appears to be a potentially effective in treating breast pain and seems generally safe for clinical application. However, this potential benefit is inconclusive due to generally weak evidence, and the findings should be further confirmed in large and rigorous trials.